Effects of Bromfenac Ophthalmic Solution on Intraocular Pressure after Phacoemulsification Surgery - Abdullah, Enas S.; Ali, Samara M.; Hussein, Zaid R. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Cataract surgery is one of the commonest surgeries. Changes in intraocular pressure (IOP) might occur after surgery and some post-operative medications might affect it.Objectives: To evaluate the effects of the non–steroidal anti–inflammatory drug Bromfenac 0.09% ophthalmic solution on intraocular pressure after phacoemulsification and to report any side effects of the drug. Method: It was a prospective study done at Jenna ophthalmic center, Baghdad- Iraq from May 2023 to January 2024 involving adult patients with cataract prepared for phacoemulsification with intraocular lens implantation. The patients were divided into two groups: Group I: received 0.09% Bromfenac ophthalmic solution twice daily in addition to Moxifloxacin 0.5% ophthalmic drops every 6 hours and Dexamethasone phosphate 0.1% ophthalmic drops every 4-6 hours post-operatively. Group II: received only Moxifloxacin 0.5% every 6 hours and Dexamethasone phosphate 0.1% ophthalmic drops every 4-6 hours without the administration of Bromfenac 0.09% ophthalmic drops post-operatively. The intraocular pressure was measured pre-operatively and 6 weeks post-operatively by Goldman applanation tonometry.Results: Eighty-seven eyes of 87 patients are enrolled in the study. The preoperative mean of intraocular pressure in group I and group II were 16.6 ± 2.37 mmHg, and 17.1 ± 3.33 mmHg respectively (not significantly different), while the postoperative mean of intraocular pressure in group I and group II, were 16.0 ± 2.32 mmHg and 16.7 ± 2.9 mmHg respectively. There were no significant changes in IOP post-operatively in either group, and the only side effect reported was punctate epithelial corneal erosion in five patients in group I. Conclusion: The effect of Bromfenac 0.09% ophthalmic solution administration postoperatively on IOP in cataract patients was insignificant. The medication resulted in punctate epithelial erosion in some patients.